An evaluation of the existing ecosan toilets in Kampala city - Mwondha, Joshua (Kampala, 2013)
Unpublished dissertation (M.ENG. CIVIL)- Makerere University, 2013.
Keywords: Sanitation, Household; Toilets -- Evaluation -- Uganda -- Kampala